CT SCAN APPLICATIONS AND RECENT ADVANCES IN TECHNOLOGY: A SCIENTIFIC RESEARCH - Hassan hamad nokhran khardali, Bader fahhad aljohani, Ali abdu moaeed khwaji, Turkey moawad ali manee, Eman alhusein Abdullah alattas, Ahmad Saoud Suliman Alotaibi, Rami Musfer Mohammed Alzahrani, Wejdan mohammed saeed algharamah, Nouf naief gafar alqhtani, Ahlam talal ahmad gonaim, (Chelonian Research Foundation, 2024)
Computed Tomography (CT) scanning has revolutionized medical diagnostics and treatment planning, offering high-resolution imaging across multiple planes of the body. Since its introduction, CT technology has advanced rapidly, with innovations improving both image quality and patient safety. This review focuses on the various applications of CT scans in medicine, the latest technological advancements, and their implications for clinical practice. It includes discussions on new techniques such as Dual-Energy CT, CT angiography, and AI-assisted imaging. Additionally, the role of CT in emerging fields, including precision medicine and minimally invasive procedures, is examined. This paper aims to provide a comprehensive overview of CT's expanding role in modern medicine, emphasizing both current uses and future directions